Method for producing silica sol, method for producing polishing composition, polishing method, method for producing semiconductor wafer, and method for producing semiconductor device

JP2026166212APending Publication Date: 2026-10-14MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025059017
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0022】 本発明の製造方法によって製造されたシリカゾルは、取り扱いが容易であり、配管の詰まりや製造装置への負荷を低減することができる。更に、本発明の製造方法によって製造されたシリカゾルは、研磨に用いられた際に被研磨体へのスクラッチや欠陥抑制効果を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166212000001
    Figure 2026166212000001
Patent Text Reader

Abstract

To provide a method for producing silica sol with low viscosity, etc. [Solution] A method for producing silica sol, comprising the following step (1): Step (1): A step of heating a dispersion of silica particles, wherein the temperature is lowered from the heating start temperature at a rate of 0.001°C / min or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing silica sol, a method for producing a polishing composition, a polishing method, a method for producing a semiconductor wafer, and a method for producing a semiconductor device. [Background technology]

[0002] Silica sol, a dispersion of silica, is widely used in polishing slurries for semiconductor components. Because silica sol contains both solid silica particles and a liquid dispersion medium, it tends to have high viscosity. High viscosity materials are difficult to handle, can cause blockages when passed through pipes, and place a heavy load on manufacturing equipment.

[0003] Furthermore, it is known that silica particles contained in silica sol exhibit abrasive action when silanol groups present on their surface chemically bond to the surface of the object being polished, and then mechanically remove them. Therefore, it is necessary to appropriately control the silanol groups on the surface of the silica particles. Methods for controlling the silanol groups on the surface of silica particles are known, including control methods in the reaction conditions during silica particle production and post-treatment. In particular, it is known that heat treatment such as pressurized heat treatment reduces the silanol groups. Patent documents 1 and 2 disclose methods for producing silica particles and silica gel, including a pressurized heat treatment step. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2022-001545 [Patent Document 2] Japanese Patent Publication No. 2023-004283 [Overview of the project] [Problems that the invention aims to solve]

[0005] As mentioned above, high viscosity of silica sol is undesirable, yet conventional methods for improving the viscosity of silica sol have not been sufficiently investigated.

[0006] Furthermore, in the production of silica particles, the behavior of silanol group reduction under different heat treatment conditions has not been sufficiently investigated. If the silanol groups are reduced too much, the silica particles and the material to be polished become less able to chemically bond, leading to scratches and defects on the surface of the material to be polished.

[0007] This invention has been made in view of these problems, and its object is to provide a method for producing silica sol with low viscosity, etc. [Means for solving the problem]

[0008] As a result of diligent research, the inventors have invented a manufacturing method that achieves a reduction in the viscosity of silica sol and a gradual reduction in the silanol groups on the surface of the silica particles in the silica sol, compared to the case where the silica particle dispersion is not heat-treated.

[0009] One aspect of the present invention is a method for producing silica sol, comprising the following step (1). Step (1): A step of heating a dispersion of silica particles, wherein the heating is performed while lowering the temperature at a rate of 0.001°C / min or more from the heating start temperature.

[0010] Aspect 2 of the present invention is a method for producing silica sol, wherein the method for producing silica sol in Aspect 1 includes the following step (2) before step (1). Step (2): A step to obtain a dispersion of silica particles containing alcohol by carrying out hydrolysis and condensation reactions of tetraalkoxysilane in the presence of an alkaline catalyst.

[0011] Aspect 3 of the present invention is a method for producing silica sol, wherein the method for producing silica sol is further comprising the following step (3) after step (2) in the method for producing silica sol in aspect 2. Step (3): a step of separating the alcohol and the alkali catalyst from the silica particle dispersion containing the alcohol.

[0012] Aspect 4 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 3, wherein the alcohol contains methanol.

[0013] Aspect 5 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 4, wherein the alkali catalyst contains ammonia.

[0014] Aspect 6 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 5, wherein the tetraalkoxysilane is tetramethoxysilane.

[0015] Aspect 7 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 6, wherein the rate of raising the temperature to the heating start temperature is 0.1°C / min to 0.5°C / min.

[0016] Aspect 8 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 7, wherein the heating start temperature is 100°C to 300°C.

[0017] Aspect 9 of the present invention is the method for producing a silica sol according to any one of Aspects 1 to 8, wherein the heating time in the step (1) is 5 minutes to 6000 minutes.

[0018] Aspect 10 of the present invention is a method for producing a polishing composition, comprising adding the silica sol obtained by the method for producing a silica sol according to any one of Aspects 1 to 9 to produce the polishing composition.

[0019] Aspect 11 of the present invention is a polishing method comprising a step of polishing using a polishing composition containing the silica sol obtained by the method for producing a silica sol according to any one of Aspects 1 to 9.

[0020] Aspect 12 of the present invention is a method for manufacturing a semiconductor wafer, comprising the polishing method described in Aspect 11.

[0021] Aspect 13 of the present invention is a method for manufacturing a semiconductor device, comprising the polishing method described in Aspect 11. [Effects of the Invention]

[0022] The silica sol produced by the manufacturing method of the present invention is easy to handle and can reduce clogging of pipes and load on manufacturing equipment. Furthermore, when used for polishing, the silica sol produced by the manufacturing method of the present invention has the effect of suppressing scratches and defects on the workpiece. [Modes for carrying out the invention]

[0023] The present invention will be described in detail below, but these are merely examples of preferred embodiments and are not limiting to these. The "~" in a numerical range indicates a range that includes the numbers before and after it. For example, "0 mass%~100 mass%" means a range that is greater than or equal to 0 mass% and less than or equal to 100 mass%.

[0024] [Method for producing silica sol] (Process (1)) The method for producing silica sol according to this embodiment includes the following step (1). Step (1): A step of heating a dispersion of silica particles, wherein the heating is performed while lowering the temperature at a rate of 0.001°C / min or more from the heating start temperature.

[0025] In step (1), the fine silica particles that have been heated and dissolved gradually precipitate as the temperature gradually decreases, so they gradually precipitate on the larger, undissolved silica particles. Therefore, the number of fine particles that would be generated if the temperature and pressure were to be reduced abruptly is reduced, resulting in a lower viscosity for the resulting silica sol. In addition, as the temperature gradually decreases, the dehydration of silanol groups slows down, so the number of silanol groups on the surface of the silica particles in the silica sol is gradually reduced.

[0026] The cooling rate in step (1) is preferably 0.01°C / min or more, more preferably 0.03°C / min or more, in order to reduce the energy required to maintain the temperature.

[0027] In the silica sol manufacturing method of this embodiment, the rate at which the temperature is raised to the heating start temperature is preferably 0.1°C / min to 0.5°C / min, more preferably 0.15°C / min to 0.4°C / min. By raising the temperature to the heating start temperature within the above range, the heating temperature can be easily adjusted, manufacturing efficiency can be increased, and the internal structure of the silica particles does not change significantly during the heating process.

[0028] The heating start temperature in step (1) is preferably 100°C to 300°C, more preferably 120°C to 200°C. By setting the heating start temperature within the above range, the energy required for heating can be reduced while sufficiently reducing the silanol groups of the silica particles.

[0029] In step (1), the heating time is preferably 5 minutes to 6000 minutes, more preferably 30 minutes to 1200 minutes. By keeping the heating time within the above range, manufacturing efficiency can be improved and the silanol group density and viscosity can be adjusted.

[0030] In this embodiment, the method for producing silica particles can increase the degree of condensation of the silica particles, so the heating step in step (1) may be replaced with a pressurized heat treatment step.

[0031] The pressure for the pressurized heat treatment is preferably 0.10 MPa to 2.3 MPa, and more preferably 0.12 MPa to 2.0 MPa. When the pressurized heat treatment pressure is 0.10 MPa or higher, the degree of condensation of silica particles can be increased. Furthermore, when the pressurized heat treatment pressure is 2.3 MPa or lower, silica particles can be produced without significantly changing the average primary particle diameter, average secondary particle diameter, cv value, or association ratio, and the dispersion stability of the silica sol is excellent.

[0032] Pressurization can be achieved by heating the silica particle dispersion to above the boiling point of the dispersion medium while it is sealed. When the silica particle aqueous dispersion is heated to above 100°C while sealed, the pressure will be equal to the saturated water vapor pressure at that temperature.

[0033] The temperature at the end of the pressurized heat treatment is preferably 80°C to 220°C, more preferably 95°C to 180°C, and particularly preferably 105°C to 160°C. If the temperature at the end of the pressurized heat treatment is 80°C or higher, the degree of condensation of silica particles can be increased. If the temperature at the end of the pressurized heat treatment is 220°C or lower, silica particles can be produced without significantly changing the average primary particle diameter, average secondary particle diameter, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.

[0034] Pressurized heat treatment is more preferably performed in an aqueous dispersion because it can increase the degree of condensation of silica particles without significantly changing the average primary particle diameter, average secondary particle diameter, cv value, or association ratio.

[0035] When performing pressurized heat treatment in an aqueous dispersion, the pH of the dispersion is preferably 6.0 to 8.0, and more preferably 6.5 to 7.8. If the pH of the pressurized heat treatment in the aqueous dispersion is 6.0 or higher, gelation of the silica sol can be suppressed. Furthermore, if the pH of the pressurized heat treatment in the aqueous dispersion is 8.0 or lower, the degree of condensation of silica particles can be increased without significantly changing the average primary particle diameter, average secondary particle diameter, cv value, or association ratio.

[0036] (Process (2)) The method for obtaining the dispersion of silica particles used in step (1) is not particularly limited, but it is preferable that the method for producing silica sol according to this embodiment includes the following step (2) before step (1). Step (2): A step to obtain a dispersion of silica particles containing alcohol by carrying out hydrolysis and condensation reactions of tetraalkoxysilane in the presence of an alkaline catalyst.

[0037] Step (2) described above may include adding a solution (B) containing tetraalkoxysilane to a solution (A) containing an alkaline catalyst. Including such a step is preferable because it makes it easier to control the hydrolysis and condensation reactions, increases the reaction rates of the hydrolysis and condensation reactions, prevents gelation of the silica particle dispersion, and makes it easier to obtain silica particles of uniform size.

[0038] The types and amounts of the alkaline catalyst and tetraalkoxysilane used in step (2) described above are the same as those described later for the alkaline catalyst and tetraalkoxysilane that may be included in solutions (A) and (B).

[0039] The hydrolysis and condensation reactions of the tetraalkoxysilane in the presence of an alkaline catalyst in step (2) above may be carried out in a solution containing a salt. The process may include a step of hydrolyzing and condensing the alkoxysilane in a solution containing a salt that decomposes or volatilizes when heated to 100°C. In the step described above, in which an alkoxysilane is hydrolyzed and condensed in a salt-containing solution, the preferred type and amount of salt used are the same as those described later for the salts that may be contained in solution (A).

[0040] Solution (A) contains an alkaline catalyst.

[0041] Solution (A) is preferable to contain water, and more preferable to contain water and a solvent other than water, because it exhibits excellent dispersibility in the reaction solution of tetraalkoxysilane. Examples of solvents other than water in solution (A) include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used individually or in combination of two or more. Among these solvents, alcohols are preferred, methanol and ethanol are more preferred, and methanol is even more preferred, because they readily dissolve tetraalkoxysilane, produce the same by-products as those used in the hydrolysis and condensation reactions, and offer excellent manufacturing convenience.

[0042] The inclusion of an alkaline catalyst in solution (A) can increase the reaction rates of the hydrolysis and condensation reactions of tetraalkoxysilanes.

[0043] Examples of alkaline catalysts in solution (A) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkaline catalysts may be used individually or in combination of two or more. Among these alkaline catalysts, ammonia is preferred because it exhibits excellent catalytic activity, allows for easy control of particle shape, suppresses the inclusion of metal impurities, and has high volatility, resulting in excellent removal after hydrolysis and condensation reactions.

[0044] When solution (A) contains water, the concentration of water is preferably 3% to 90% by mass, and more preferably 5% to 50% by mass, of 100% by mass of solution (A). When the concentration of water in solution (A) is 3% by mass or more, it is easier to control the hydrolysis reaction rate of tetraalkoxysilane. Furthermore, when the concentration of water in solution (A) is 90% by mass or less, the reaction balance between the hydrolysis reaction and the condensation reaction is good, and it is easier to control the particle shape.

[0045] The concentration of the alkaline catalyst in solution (A) is preferably maintained at 0.5% to 4.0% by mass, more preferably at 1.0% to 3.5% by mass, and even more preferably at 1.5% to 3.0% by mass, based on 100% by mass of solution (A). When the concentration of the alkaline catalyst in solution (A) is 0.5% by mass or higher, aggregation of silica particles is suppressed, and the dispersion stability of silica particles in the dispersion is excellent. Furthermore, when the concentration of the alkaline catalyst in solution (A) is 4.0% by mass or lower, the reaction does not proceed excessively quickly, and the reaction is well controllable.

[0046] Solution (A) may contain salt. There are no particular restrictions on the salts in solution (A), and examples include ammonium acetate, ammonium tartrate, ammonium citrate, ammonium acetate, ammonium benzoate, ammonium malate, ammonium butyrate, ammonium propionate, ammonium oxalate, ammonium maleate, ammonium succinate, ammonium glutarate, ammonium fumarate, ammonium adipicate, ammonium sorbate, ammonium palmitate, ammonium laurate, ammonium sebacate, ammonium pimarate, ammonium stearate, sodium acetate, ammonium acetate, sodium carbonate, sodium hydrogen phosphate, ammonium hydrogen phosphate, and diphosphate. Examples include sodium hydrogen, ammonium dihydrogen phosphate, sodium citrate, ammonium citrate, ammonium nitrate, sodium sulfate, ammonium sulfate, sodium borate, ammonium borate, sodium butyrate, ammonium butyrate, sodium propionate, ammonium carbamidate, tetramethoxyammonium acetate, tetraethoxyammonium acetate, tetrapropoxyammonium acetate, tetrabutoxyammonium acetate, tetramethoxyammonium benzoate, tetraethoxyammonium benzoate, tetrapropoxyammonium benzoate, tetrabutoxyammonium benzoate, tetraethylammonium bicarbonate, ammonium carbonate, sodium bicarbonate, etc. These salts may be used individually or in combination of two or more. As for the salts, neutral salts, i.e., salts of a weak acid and a weak base or a strong acid and a strong base, are preferred because they minimize the change in pH of the reaction solution due to the addition and do not alter the reaction rate of tetraalkoxysilane.

[0047] Furthermore, as the salt, a salt that decomposes and volatilizes when heated is preferred, and a salt that decomposes or volatilizes when heated to 100°C is more preferred, as this avoids contamination of the final silica sol and the silica particles contained therein, and broadens the industrial application range of the silica sol and silica particles. These salts do not need to decompose or volatilize completely when they reach 100°C; it is sufficient if decomposition or volatilization begins at 100°C. Specifically, ammonium nitrate, ammonium carbamidate, ammonium carbonate, and ammonium bicarbonate are preferred, with ammonium bicarbonate being more preferred.

[0048] By adding salt to solution (A), the aggregation of silica particles is promoted, which allows for adjustment of physical properties such as viscosity reduction and zeta potential adjustment.

[0049] When solution (A) contains a salt, there are no particular restrictions on the amount of salt used, but the molar ratio of the amount of salt to the amount of alkaline catalyst used is preferably 0.0005 to 0.045, more preferably 0.00125 to 0.02, and even more preferably 0.0025 to 0.01. The molar ratio can be determined in detail by the following formula. (Molar ratio) = (Amount of salt used (moles)) / (Amount of alkaline catalyst used (moles)) When the molar ratio of the amount used is 0.0005 or higher, the particle size can be effectively adjusted to be larger. Furthermore, when it is 0.045 or lower, the aggregation and precipitation of silica particles can be suppressed.

[0050] When solution (A) contains a solvent other than water, it is preferable that the concentration of the solvent other than water be the remainder of the water, alkaline catalyst, and the salt described above.

[0051] Solution (B) contains tetraalkoxysilane.

[0052] Examples of tetraalkoxysilanes in solution (B) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. These tetraalkoxysilanes may be used individually or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, because they undergo rapid hydrolysis, leave little unreacted residue, have excellent productivity, and allow for easy acquisition of a stable silica sol.

[0053] While raw materials other than tetraalkoxysilane, such as low-level condensates of tetraalkoxysilane, may be used as raw materials for silica particles, it is preferable that, due to their excellent reactivity, the silica particles consist of 100% by mass of tetraalkoxysilane at 50% or more by mass and raw materials other than tetraalkoxysilane at 50% or less by mass, and more preferably 80% or more by mass of tetraalkoxysilane and raw materials other than tetraalkoxysilane at 20% or less by mass.

[0054] Solution (B) may contain only tetraalkoxysilane without a solvent, but it is preferable to include a solvent because it provides excellent dispersibility of the tetraalkoxysilane in the reaction solution. Examples of solvents in solution (B) include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used individually or in combination of two or more. Among these solvents, alcohols are preferred, methanol and ethanol are more preferred, and methanol is even more preferred, because the by-products used in the hydrolysis and condensation reactions are the same, and they offer excellent manufacturing convenience.

[0055] The concentration of tetraalkoxysilane in solution (B) is preferably 60% to 95% by mass, and more preferably 70% to 90% by mass, based on 100% by mass of solution (B). When the concentration of tetraalkoxysilane in solution (B) is 60% by mass or higher, the reaction solution tends to become more homogeneous. Furthermore, when the concentration of tetraalkoxysilane in solution (B) is 95% by mass or lower, the formation of gel-like substances can be suppressed.

[0056] The concentration of the solvent in solution (B) is preferably 5% to 40% by mass, and more preferably 10% to 30% by mass, based on 100% by mass of solution (B). If the concentration of the solvent in solution (B) is 5% by mass or higher, the formation of gel-like substances can be suppressed. Also, if the concentration of the solvent in solution (B) is 40% by mass or lower, the reaction solution tends to become more homogeneous.

[0057] The rate at which solution (B) is added per unit time relative to the volume of solution (A) is preferably 0.02 kg / hour / L to 1.3 kg / hour / L, and more preferably 0.05 kg / hour / L to 0.8 kg / hour / L. When the rate at which solution (B) is added is 0.02 kg / hour / L or higher, the productivity of silica particles is excellent. Furthermore, when the rate at which solution (B) is added is 1.3 kg / hour / L or lower, the formation of gel-like substances can be suppressed.

[0058] In another embodiment, silica particles can also be obtained by a manufacturing method that includes the step of adding a solution (B) containing tetraalkoxysilane and a solution (C) containing water to a solution (A) containing an alkaline catalyst. Solution (C) is a solution containing water, and preferably also contains an alkaline catalyst.

[0059] Examples of alkaline catalysts that solution (C) may contain include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkaline catalysts may be used individually or in combination of two or more. Among these alkaline catalysts, ammonia is preferred because it exhibits excellent catalytic activity, allows for easy control of particle shape, suppresses the inclusion of metal impurities, and has high volatility, resulting in excellent removal after hydrolysis and condensation reactions.

[0060] Solution (C) contains water as a solvent. Other solvents include methanol, ethanol, propanol, isopropanol, and ethylene glycol. One solvent other than water may be used alone, or two or more may be used in combination. Among the solvents of solution (C), water alone or a combination of water and alcohol is preferred, and water alone is more preferred, because the by-products used in the hydrolysis and condensation reactions are the same, and it is convenient in manufacturing.

[0061] The concentration of the alkaline catalyst in solution (C) is preferably 0% to 10% by mass out of 100% by mass of solution (C). The alkaline catalyst in solution (C) may be 0% by mass, i.e., not present at all, but if an alkaline catalyst is present, its concentration is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more. When the concentration of the alkaline catalyst in solution (C) is 0.5% by mass or more, it is easy to adjust the concentration of the alkaline catalyst in the reaction solution from the start to the end of the reaction. Furthermore, from the viewpoint of minimizing fluctuations in the concentration of the alkaline catalyst in the reaction solution, the concentration of the alkaline catalyst in solution (C) is preferably 10% by mass or less, and more preferably 6% by mass or less.

[0062] The concentration of water in solution (C) is preferably 90% to 100% by mass out of 100% by mass of solution (C). While solution (C) may consist solely of water at 100% by mass, if other components are present, the water concentration is preferably 99.5% by mass or less, and more preferably 99% by mass or less. From the viewpoint of minimizing fluctuations in the concentration of the alkaline catalyst in the reaction solution, the water concentration in solution (C) is preferably 90% by mass or more, and more preferably 94% by mass or more. Furthermore, if the water concentration in solution (C) is 99.5% by mass or less, it is easier to adjust the concentration of the alkaline catalyst in the reaction solution from the start to the end of the reaction.

[0063] The concentration of the solvent other than water in solution (C) is preferably equal to the concentration of the remainder of the water, or the remainder of the water and alkaline catalyst.

[0064] It is preferable to add solution (B), or solution (B) and solution (C), to solution (A). Adding solution (B), or solution (B) and solution (C), to solution (A) improves the mixability of each component in the reaction solution, suppresses abnormal reactions in the air, and makes it easier to control the particle shape, especially when using a highly volatile alkaline catalyst such as ammonia and when proceeding with hydrolysis and condensation reactions at high reaction temperatures. Adding to a liquid means adding below the liquid surface, and by setting the supply outlet for solution (B), or the supply outlet for both solution (B) and solution (C), below the liquid surface of solution (A), solution (B), or solution (B) and solution (C) can be added to solution (A).

[0065] When adding solutions (B) and (C), the timing of adding solutions (B) and (C) to solution (A) may be the same or alternate, but it is preferable that the timing be the same, as this minimizes variations in the reaction composition and avoids complicated procedures.

[0066] The pH in the step of hydrolyzing and condensing tetraalkoxysilane is 8.0 to 14, preferably 8.2 to 13, and more preferably 8.5 to 12. When the pH in the above step is 8.0 or higher, the reaction rate of the hydrolysis and condensation reactions is excellent, and the aggregation of silica particles can be suppressed. Furthermore, when the pH in the above step is 14 or lower, the shape of the silica particles can be easily controlled, and the smoothness of the silica particle surface is excellent.

[0067] The method for producing silica sol according to this embodiment preferably includes a step of carrying out the hydrolysis and condensation reactions of alkoxysilane at 5°C or higher, and more preferably a step of carrying out the reactions at 20°C or higher. When the reaction temperature is 5°C or higher, the reaction rates of the hydrolysis and condensation reactions of alkoxysilane are moderately improved, and the four bonds of the silicon atoms can form siloxane bonds before particle growth progresses. This reduces the number of silanol groups inside the fine pores present in the particles. As a result, when the particles are dispersed in water, the charge of the particles is reduced, which is preferable because it reduces the proportion of water bound to the particles. Furthermore, when the reaction temperature is 60°C or lower, an excellent balance is achieved between the hydrolysis reaction rate and the condensation reaction rate.

[0068] The concentration of water in the reaction system for the hydrolysis and condensation reactions is preferably maintained at 3% to 90% by mass, more preferably at 5% to 30% by mass, and even more preferably at 6% to 25% by mass, out of 100% by mass of the total amount in the reaction system. When the water concentration in the reaction system is 3% by mass or higher, it is easier to control the hydrolysis reaction rate of tetraalkoxysilane. Furthermore, when the water concentration in the reaction system is 90% by mass or lower, the reaction balance between the hydrolysis reaction and the condensation reaction is good, and it is easier to control the particle shape.

[0069] The concentration of the alkaline catalyst in the reaction system for hydrolysis and condensation reactions is preferably maintained at 0.5% to 4.0% by mass, more preferably at 1.5% to 3.5% by mass, and even more preferably at 2.2% to 3.0% by mass, based on 100% by mass of the total amount in the reaction system. When the concentration of the alkaline catalyst in the reaction system is 0.5% by mass or higher, the aggregation of silica particles is suppressed, and the dispersion stability of silica particles in the dispersion is excellent. Furthermore, when the concentration of the alkaline catalyst in the reaction system is 4.0% by mass or lower, the reaction does not proceed excessively quickly, and the reaction is well controllable.

[0070] (Step (3)) The method for producing silica sol according to this embodiment preferably includes the following step (3) after step (2). Step (3): A step of separating the alcohol and the alkaline catalyst from the dispersion of silica particles containing the alcohol.

[0071] Step (3) may be performed after step (2), but it is preferable to perform it before step (1) to avoid the risks associated with handling hazardous or toxic substances under high temperature and pressure conditions.

[0072] This separation process has the advantage of allowing the resulting dispersion of silica particles to be handled as a safe substance, not a hazardous or toxic material.

[0073] Methods for separating alcohol and an alkaline catalyst from a dispersion of silica particles containing alcohol include distillation and membrane separation, with distillation being preferred.

[0074] In step (3), the order of the steps for separating the alcohol and separating the alkaline catalyst is not important, and they may be separated simultaneously.

[0075] Examples of the alcohols mentioned above include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These may be used individually or in combination of two or more. Among these alcohols, methanol and ethanol are preferred, with methanol being more preferred. The reason for their preference is the same as the reason for their preference as solvents in solution (A) and solution (B) in step (2).

[0076] (Step (4)) The method for producing silica particles according to this embodiment may further include the following step (4), since it is possible to remove unnecessary components and add necessary components. Step (4): Concentrating the resulting silica particle dispersion and adding a dispersion medium.

[0077] In step (4), the concentration of the silica particle dispersion and the addition of the dispersion medium may be performed in either order.

[0078] Step (4) may be performed after step (2), but it is preferable to perform it before step (1) to avoid the risks associated with handling hazardous materials and toxic substances under high temperature and pressure conditions.

[0079] The method for concentrating a dispersion of silica particles is not particularly limited and can include, for example, heat concentration or membrane concentration. To concentrate a dispersion of silica particles by a heating concentration method, the dispersion can be heated and concentrated under normal pressure or under reduced pressure.

[0080] For concentrating a dispersion of silica particles by membrane concentration, membrane separation by ultrafiltration is preferred. Here, the primary purpose of ultrafiltration is to remove unwanted components, such as intermediate products. The molecular weight cutoff of the ultrafiltration membrane used here is selected to match the intermediate products in the dispersion, so that these intermediate products can be filtered and separated and removed. Materials for ultrafiltration membranes include polysulfone, polyacrylonitrile, sintered metal, ceramic, and carbon. Examples of ultrafiltration membrane shapes include spiral, tubular, and hollow fiber types.

[0081] Examples of dispersion media to be added to a dispersion of silica particles include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These dispersion media may be used individually or in combination of two or more. Among these dispersion media, water or alcohol is preferred, and water or methanol is more preferred, due to their excellent affinity with silica particles.

[0082] (others) The method for producing silica sol according to this embodiment preferably includes the following steps (5) or (6). In order to reduce the energy required for concentrating the dispersion medium, the following steps (5) or (6) are preferably performed after step (2) and before step (1), and more preferably after step (2) and before or simultaneously with step (3). Step (5): Step of concentrating the silica particle dispersion. Step (6): Concentrating the silica particle dispersion and adding a dispersion medium.

[0083] The order in which the silica particle dispersion is concentrated and the dispersion medium is added in step (6) may be carried out.

[0084] The method for concentrating a dispersion of silica particles is not particularly limited and can include, for example, heat concentration or membrane concentration. To concentrate a dispersion of silica particles by a heating concentration method, the dispersion can be heated and concentrated under normal pressure or under reduced pressure. For concentrating a dispersion of silica particles using a membrane concentration method, membrane separation by ultrafiltration is preferred. The molecular weight cutoff of the ultrafiltration membrane used here should be selected to match the particle size of the silica particles in the dispersion, allowing for filtration separation and concentration. Materials for ultrafiltration membranes include polysulfone, polyacrylonitrile, sintered metal, ceramic, and carbon. Examples of ultrafiltration membrane shapes include spiral, tubular, and hollow fiber types.

[0085] Furthermore, examples of dispersion media to be added to the silica particle dispersion include water, methanol, ethanol, propanol, isopropanol, ethylene glycol, and other alcohols. These dispersion media may be used individually or in combination of two or more. Among these dispersion media, water and alcohol are preferred, with water being more preferred, due to their excellent affinity with silica particles.

[0086] The method for producing silica sol according to this embodiment may include steps for removing unnecessary components and adding necessary components from the components of the silica particle dispersion.

[0087] The method for producing silica sol according to this embodiment may include a filtration step in order to remove coarse particles or to avoid aggregation by fine particles. Methods of filtration include, for example, natural filtration under atmospheric pressure, reduced pressure filtration, pressure filtration, and centrifugal filtration. Filtration may be performed at any time and any number of times, but it is preferable to perform it immediately before preparing the polishing composition because it improves the storage stability and polishing properties of the polishing composition.

[0088] [Silica sol] The silica sol obtained by the manufacturing method according to this embodiment contains silica particles.

[0089] The viscosity of the silica sol described above is preferably 0 to 150 mPa·s, more preferably 0 to 100 mPa·s, and particularly preferably 0 to 85 mPa·s at 25°C. Having the viscosity of the silica sol within this range makes it easy to handle and reduces clogging of pipes and load on manufacturing equipment.

[0090] The viscosity of silica sol can be measured using an E-type viscometer "TVE-25L" (model name, manufactured by Toki Sangyo Co., Ltd.) under conditions of 25°C and a shear rate of 150 / second.

[0091] Silica sol may be produced by using a dispersion of silica particles as is, or by removing unnecessary components from the dispersion of silica particles and adding necessary components. The silica sol obtained by the manufacturing method of this embodiment preferably contains silica particles and a dispersion medium.

[0092] Examples of dispersion media in silica sols include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These dispersion media in silica sols may be used individually or in combination of two or more. Among these dispersion media in silica sols, water and alcohol are preferred, with water being more preferred, due to their excellent affinity for silica particles.

[0093] The content of the dispersion medium in the silica sol is preferably 50% to 97% by mass, more preferably 60% to 96% by mass, and even more preferably 70% to 95% by mass, based on 100% by mass of the total silica sol. When the content of the dispersion medium in the silica sol is 50% by mass or more, aggregation of silica particles in the silica sol and polishing composition can be suppressed, resulting in excellent storage stability of the silica sol and polishing composition. Furthermore, when the content of the dispersion medium in the silica sol is 97% by mass or less, the polishing rate for the workpiece, such as silicon wafers, is excellent.

[0094] The content of silica particles and dispersion medium in the silica sol can be set to a desired range by removing unnecessary components and adding necessary components from the components of the resulting silica particle dispersion.

[0095] In addition to silica particles and dispersion medium, silica sol may contain other components as needed, such as oxidizing agents, preservatives, fungicides, pH adjusters, pH buffers, surfactants, chelating agents, and antimicrobial biocides, to the extent that it does not impair its performance. In particular, since silica sol has excellent storage stability, it is preferable to include an antimicrobial biocide in the silica sol.

[0096] Examples of antimicrobial biocides include hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salt, ethylenediamine, glutaraldehyde, methyl p-hydroxybenzoate, and sodium chlorite. These antimicrobial biocides may be used individually or in combination of two or more. Among these antimicrobial biocides, hydrogen peroxide is preferred due to its excellent affinity for silica sol. Antimicrobial biocides include what are commonly known as disinfectants.

[0097] The content of the antimicrobial biocide in the silica sol is preferably 0.0001% to 10% by mass, and more preferably 0.001% to 1% by mass, based on 100% by mass of the total silica sol. When the content of the antimicrobial biocide in the silica sol is 0.0001% by mass or more, the silica sol exhibits excellent storage stability. When the content of the antimicrobial biocide in the silica sol is 10% by mass or less, the original performance of the silica sol is not impaired.

[0098] The pH of the silica sol is preferably 6.0 to 8.0, and more preferably 6.5 to 7.8. When the pH of the silica sol is 6.0 or higher, it exhibits excellent dispersion stability and can suppress the aggregation of silica particles. Furthermore, when the pH of the silica sol is 8.0 or lower, it prevents the dissolution of silica particles and exhibits excellent long-term storage stability. The pH of silica sol can be set to a desired range by adding a pH adjusting agent.

[0099] (Silica particles) The preferred physical properties of silica particles in the silica sol produced by the silica sol production method of this embodiment will be described below.

[0100] The surface silanol group density of silica particles is 1 / nm. 2 ~20 pieces / nm 2 Preferably, 1 particle / nm 2 ~14 pieces / nm 2 More preferably, 1 pc / nm 2 ~8 pieces / nm 2 This is even more preferable. The surface silanol group density of the silica particles is 1 / nm. 2 As a result, the silica particles have appropriate surface resilience, and the dispersion stability of the silica sol is excellent. Furthermore, the surface silanol group density of the silica particles is 20 groups / nm. 2 The following conditions are advantageous because they suppress the formation of chemical bonds between silica particles and the workpiece, thereby preventing particle adhesion after polishing. Furthermore, when the surface silanol group density of the silica particles is within the above range, the silica sol has a scratch and defect suppression effect on the workpiece when used for polishing. Furthermore, by the method for producing a silica sol of the present embodiment, the silanol group density can be easily controlled within the above range by moderately reducing the silanol groups on the surface of the silica particles of the silica sol. Therefore, when different substances are mixed in the object to be polished, effects such as selective polishing for the substances, for example, polishing the object to be polished that is desired to be polished and not polishing the object to be polished that is not desired to be polished can be expected.

[0101] The surface silanol group density of the silica particles is measured by the Sears method. Specifically, the measurement and calculation are performed under the conditions shown below. A silica sol corresponding to 1.5 g of silica particles is collected, and pure water is added to adjust the liquid volume to 90 mL. Under an environment of 25°C, a 0.1 mol / L hydrochloric acid aqueous solution is added until the pH reaches 3.6, 30 g of sodium chloride is added, pure water is gradually added to completely dissolve the sodium chloride, and finally pure water is added until the total volume of the test liquid reaches 150 mL, to obtain the test liquid. The obtained test liquid is placed in an automatic titrator, and a 0.1 mol / L sodium hydroxide aqueous solution is added dropwise to measure the titration amount A (mL) of the 0.1 mol / L sodium hydroxide aqueous solution required for the pH to change from 4.0 to 9.0.

[0102] Using the following formula (1), the consumption V (mL) of the 0.1 mol / L sodium hydroxide aqueous solution required for the pH per 1.5 g of silica particles to change from 4.0 to 9.0 is calculated, and using the following formula (2), the surface silanol group density ρ (pieces / nm 2 ) of the silica particles is calculated. V=(A×f×100×1.5) / (W×C) ··· (1) A: Titration amount (mL) of the 0.1 mol / L sodium hydroxide aqueous solution required for the pH per 1.5 g of silica particles to change from 4.0 to 9.0 f: Titer of the 0.1 mol / L sodium hydroxide aqueous solution used C: Concentration (mass%) of silica particles in the silica sol W: Collected amount (g) of the silica sol ρ=(B×NA) / (10 18 ×M×SBET) ··· (2) The amount of sodium hydroxide (mol) required to change the pH of 1.5g of silica particles from 4.0 to 9.0, calculated from B:V. NA: Avogadro's number (particles / mol) M: Silica particle amount (1.5g) SBET: Specific surface area (m²) of silica particles measured when calculating the average primary particle diameter. 2 / g)

[0103] A higher refractive index of silica particles leads to a higher atomic density, making it easier to maintain mechanical strength. Therefore, the refractive index of silica particles is preferably 1.390 or higher, more preferably 1.400 or higher, and even more preferably 1.410 or higher. Furthermore, since it is preferable for silica to maintain an amorphous structure, the refractive index is preferably 1.550 or lower, more preferably 1.500 or lower, and even more preferably 1.450 or lower. Various methods can be considered for controlling the refractive index of silica particles; for example, the refractive index of silica particles can be increased by raising the reaction temperature.

[0104] The refractive index of silica particles is determined by adding special grade 2-propanol and special grade toluene in varying ratios to a container containing silica particles. The supernatant liquid, when the silica particles in the container become clear, is measured using an Abbe refractometer, and the refractive index at that time is defined as the refractive index of the silica particles.

[0105] The silica particles are preferably amorphous. In this case, a moderate amount of silanol groups are present on the surface of the silica particles, and during the polishing process, chemical interactions occur between the silica particles and the object to be polished via the silanol groups, resulting in smooth polishing. The amorphous nature of silica particles can be confirmed by the halo pattern observed in wide-angle X-ray scattering measurements.

[0106] The metal impurity content of the silica particles is preferably 5 ppm or less, and more preferably 1 ppm or less. When the metal impurity content of silica particles is 5 ppm or less, it is preferable because, in the polishing of silicon wafers for semiconductor devices, contamination caused by metal impurities adhering to the surface of the object being polished and the resulting impact on wafer properties are reduced. Furthermore, it is preferable because the degradation of quality caused by metal impurities adhering to the surface of the object being polished diffusing into the wafer, and the decrease in performance of semiconductor devices manufactured using such wafers, are reduced.

[0107] Furthermore, when the metal impurity content of the silica particles is 5 ppm or less, it is preferable because the influence on the polishing rate due to changes in the chemical properties (acidity, etc.) of the surface silanol groups (which exhibit acidity) and changes in the steric environment of the silica particle surface (ease of aggregation of silica particles, etc.) due to coordination interactions between the acidic surface silanol groups and the metal impurities is reduced.

[0108] In this specification, the metal impurity content of silica particles is a value measured by inductively coupled plasma mass spectrometry (ICP-MS). Specifically, a silica sol containing 0.4 g of silica particles is accurately weighed, sulfuric acid and hydrofluoric acid are added, the mixture is heated, dissolved, and evaporated, and pure water is added to the remaining sulfuric acid droplets to create a test solution with a total volume of exactly 10 g. This test solution is then measured using an inductively coupled plasma mass spectrometer. The target metals are sodium, potassium, iron, aluminum, calcium, magnesium, zinc, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel, and the sum of the content of these metals is defined as the metal impurity content.

[0109] The metal impurity content of silica particles can be reduced to 5 ppm or less by performing hydrolysis and condensation reactions using alkoxysilane as the main raw material to obtain silica particles. In methods involving the deionization of alkali silicates such as water glass, residual sodium and other substances from the raw materials remain, making it extremely difficult to reduce the metal impurity content of silica particles to 5 ppm or less.

[0110] The average primary particle diameter of the silica particles is preferably 5 nm to 200 nm, more preferably 10 nm to 150 nm, and even more preferably 25 nm to 100 nm. When the average primary particle diameter of the silica particles is 5 nm or more, the storage stability of the silica sol is excellent. Furthermore, when the average primary particle diameter of the silica particles is 200 nm or less, the surface roughness and scratches of the polished object, such as silicon wafers, can be reduced, and the sedimentation of silica particles can be suppressed.

[0111] The average primary particle diameter of silica particles is measured by the BET method. Specifically, the specific surface area of ​​silica particles is measured using an automatic specific surface area measuring device, and the average primary particle diameter is calculated using the following formula (3). Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ... (3)

[0112] The average primary particle size of silica particles can be set to a desired range depending on the manufacturing conditions of the silica particles.

[0113] The average secondary particle diameter (nm) of the silica particles is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 50 nm or more. Furthermore, it is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less. When the average secondary particle diameter of silica particles is 10 nm or larger, the removal of particles and other contaminants during post-polishing cleaning is excellent, and the storage stability of the silica sol is excellent. Furthermore, when the average secondary particle diameter of silica particles is 300 nm or smaller, the surface roughness and scratches of the polished object, such as silicon wafers, can be reduced during polishing, the removal of particles and other contaminants during post-polishing cleaning is excellent, and the sedimentation of silica particles can be suppressed. For example, the average secondary particle size of silica particles can be set to 10 nm to 300 nm.

[0114] The average secondary particle size of silica particles is measured by the DLS method. Specifically, it is measured using a dynamic light scattering particle size analyzer.

[0115] The average secondary particle size of silica particles can be set to a desired range depending on the manufacturing conditions of the silica particles. For example, when the reaction temperature during the synthesis of silica particles is low, the average secondary particle size of the silica particles tends to be larger, while when the reaction temperature during the synthesis of silica particles is high, the average secondary particle size of the silica particles tends to be smaller.

[0116] The CV value of the silica particles is preferably 10% to 50%, more preferably 15% to 40%, and even more preferably 20% to 30%. When the CV value of the silica particles is 10% or higher, the polishing rate on the workpiece, such as silicon wafers, is excellent, resulting in superior silicon wafer productivity. Furthermore, when the CV value of the silica particles is 50% or lower, the surface roughness and scratches on the workpiece, such as silicon wafers, during polishing can be reduced, and the removal of particles and other contaminants during cleaning after polishing is excellent.

[0117] The cv value of silica particles is calculated by measuring the average secondary particle diameter of the silica particles using a dynamic light scattering particle diameter analyzer and then using the following formula (4). CV value = (Standard deviation (nm) / Average secondary particle size (nm)) × 100 ... (4)

[0118] The association ratio of silica particles is preferably 1.0 to 4.0, more preferably 1.1 to 2.0, and even more preferably 1.2 to 1.8. When the association ratio of silica particles is 1.0 or higher, the polishing rate for the workpiece, such as silicon wafers, is excellent, and the productivity of silicon wafers is excellent. Furthermore, when the association ratio of silica particles is 4.0 or lower, the surface roughness and scratches of the workpiece, such as silicon wafers, during polishing can be reduced, and the aggregation of silica particles can be suppressed.

[0119] The association ratio of silica particles is calculated using the following formula (5) from the average primary particle diameter and the average secondary particle diameter measured using the aforementioned measurement method. Association ratio = average secondary particle diameter / average primary particle diameter (5)

[0120] Silica particles have a low content of metal impurities and possess moderate mechanical strength and flexibility due to trace amounts of residual alkoxy groups within the particles. Therefore, it is preferable that alkoxysilane condensates be the main component, more preferably tetraalkoxysilane condensates, and even more preferably tetramethoxysilane condensates. The main component refers to a component that accounts for 50% or more by mass of 100% by mass of all components constituting the silica particles. To obtain silica particles mainly composed of alkoxysilane condensates, it is preferable to use alkoxysilane as the main raw material. To obtain silica particles mainly composed of tetraalkoxysilane condensates, it is preferable to use tetraalkoxysilane as the main raw material. To obtain silica particles mainly composed of tetramethoxysilane condensates, it is preferable to use tetramethoxysilane as the main raw material. The main raw material refers to a raw material that accounts for 50% or more by mass of the total raw materials constituting the silica particles (100% by mass).

[0121] The presence of alkoxysilane condensates as the main component can be confirmed by examining the presence of alkoxy groups in the silica particles. While there are no specific restrictions on the method used to examine the presence of alkoxy groups, methods such as measuring 13C solid-state NMR for silica particles or measuring the alcohol content in an alkaline solution containing dissolved silica particles can be used.

[0122] The silica particle content in the silica sol is preferably 3% to 50% by mass, more preferably 4% to 40% by mass, and even more preferably 5% to 30% by mass, based on 100% by mass of the total silica sol. When the silica particle content in the silica sol is 3% by mass or more, the polishing rate for the workpiece, such as silicon wafers, is excellent. Furthermore, when the silica particle content in the silica sol is 50% by mass or less, aggregation of silica particles in the silica sol and polishing composition can be suppressed, resulting in excellent storage stability for the silica sol and polishing composition.

[0123] [Method for producing abrasive composition] The method for producing the polishing composition of this embodiment includes producing a polishing composition by adding the silica sol obtained by the silica sol production method of this embodiment, and preferably includes producing a polishing composition by adding the silica sol obtained by the silica sol production method of this embodiment to a water-soluble polymer. The polishing composition can be obtained by mixing silica sol, water-soluble polymer, and other components as needed. However, considering storage and transportation, it may be prepared at a high concentration first and then diluted with water or other solvents immediately before polishing.

[0124] The polishing composition obtained by the manufacturing method according to this embodiment contains the silica sol obtained by the manufacturing method according to this embodiment. The above polishing composition preferably contains a water-soluble polymer in addition to silica sol.

[0125] Water-soluble polymers enhance the wettability of the polishing composition to the workpiece, such as silicon wafers. Preferably, the water-soluble polymer has functional groups with high water affinity. These water-affinity functional groups have a high affinity for the surface silanol groups of silica particles, resulting in a more stable dispersion of silica particles and water-soluble polymers in close proximity within the polishing composition. Therefore, during polishing of workpieces such as silicon wafers, the effects of silica particles and water-soluble polymers function synergistically.

[0126] Examples of water-soluble polymers include cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone, copolymers having a polyvinylpyrrolidone skeleton, and polymers having a polyoxyalkylene structure.

[0127] Examples of cellulose derivatives include hydroxyethylcellulose, hydrolyzed hydroxyethylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxypropylmethylcellulose, methylcellulose, ethylcellulose, ethylhydroxyethylcellulose, and carboxymethylcellulose.

[0128] Examples of copolymers having a polyvinylpyrrolidone skeleton include graft copolymers of polyvinyl alcohol and polyvinylpyrrolidone.

[0129] Examples of polymers having a polyoxyalkylene structure include polyoxyethylene, polyoxypropylene, and copolymers of ethylene oxide and propylene oxide.

[0130] These water-soluble polymers may be used individually or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethylcellulose is more preferred, because they have a high affinity for the silanol groups on the surface of silica particles and act synergistically to provide good hydrophilicity to the surface of the object to be polished.

[0131] The mass-average molecular weight of the water-soluble polymer is preferably 1,000 to 3,000,000, more preferably 5,000 to 2,000,000, and even more preferably 10,000 to 1,000,000. When the mass-average molecular weight of the water-soluble polymer is 1,000 or more, the hydrophilicity of the polishing composition is improved. Furthermore, when the mass-average molecular weight of the water-soluble polymer is 3,000,000 or less, it exhibits excellent affinity with silica sol and provides excellent polishing rate for materials to be polished, such as silicon wafers.

[0132] The mass-average molecular weight of water-soluble polymers is measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as the mobile phase, based on polyethylene oxide.

[0133] The content of water-soluble polymers in the abrasive composition is preferably 0.02% to 10% by mass, and more preferably 0.05% to 5% by mass, based on 100% by mass of the total amount of the abrasive composition. When the content of water-soluble polymers in the abrasive composition is 0.02% by mass or more, the hydrophilicity of the abrasive composition is improved. Furthermore, when the content of water-soluble polymers in the abrasive composition is 10% by mass or less, aggregation of silica particles during the preparation of the abrasive composition can be suppressed.

[0134] In addition to silica sol and water-soluble polymer, the above-mentioned abrasive composition may optionally contain other components such as basic compounds, polishing accelerators, surfactants, hydrophilic compounds, preservatives, fungicides, pH adjusters, pH buffers, surfactants, chelating agents, and antimicrobial biocides, to the extent that it does not impair its performance. In particular, it is preferable to include a basic compound in the polishing composition because it allows for chemical polishing (chemical etching) by applying a chemical action to the surface of the workpiece, such as a silicon wafer, and the polishing speed of the workpiece, such as a silicon wafer, can be improved due to the synergistic effect with the silanol groups on the surface of the silica particles.

[0135] Examples of basic compounds include organic basic compounds, alkali metal hydroxides, alkali metal bicarbonates, alkali metal carbonates, and ammonia. These basic compounds may be used individually or in combination of two or more. Among these basic compounds, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium bicarbonate, and ammonium carbonate are preferred due to their high water solubility and excellent affinity with silica particles and water-soluble polymers. Ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, and ammonia is even more preferred.

[0136] The content of basic compounds in the polishing composition is preferably 0.001% to 5% by mass, and more preferably 0.01% to 3% by mass, based on 100% by mass of the total amount of the polishing composition. When the content of basic compounds in the polishing composition is 0.001% by mass or more, the polishing speed of the workpiece, such as silicon wafers, can be improved. Furthermore, when the content of basic compounds in the polishing composition is 5% by mass or less, the stability of the polishing composition is excellent.

[0137] The pH of the abrasive composition is preferably 8.0 to 12.0, and more preferably 9.0 to 11.0. When the pH of the abrasive composition is 8.0 or higher, aggregation of silica particles in the abrasive composition can be suppressed, and the dispersion stability of the abrasive composition is excellent. Furthermore, when the pH of the abrasive composition is 12.0 or lower, dissolution of silica particles can be suppressed, and the stability of the abrasive composition is excellent. The pH of the abrasive composition can be set to a desired range by adding a pH adjusting agent.

[0138] [Polishing method] The polishing method according to this embodiment is a method of polishing using a polishing composition containing silica sol obtained by the silica sol manufacturing method according to this embodiment. It is preferable to use the polishing composition described above. Specific polishing methods include, for example, pressing the surface of a silicon wafer against a polishing pad, dropping the polishing composition according to this embodiment onto the polishing pad, and polishing the surface of the silicon wafer.

[0139] [Method for manufacturing semiconductor wafers] The semiconductor wafer manufacturing method according to this embodiment includes a polishing method according to this embodiment, and the specific polishing composition and polishing method are as described above. Examples of semiconductor wafers include silicon wafers and compound semiconductor wafers.

[0140] [Manufacturing method for semiconductor devices] The method for manufacturing a semiconductor device according to this embodiment includes a polishing method according to this embodiment, and the specific polishing composition and polishing method are as described above.

[0141] [Application] The silica sol and silica particles obtained by the manufacturing method according to this embodiment can be suitably used for polishing applications. For example, they can be used for polishing semiconductor materials such as silicon wafers, electronic materials such as hard disk substrates, polishing in the planarization process when manufacturing integrated circuits (chemical mechanical polishing), polishing synthetic quartz glass substrates used in photomasks and liquid crystals, and polishing magnetic disk substrates. They are particularly suitable for polishing silicon wafers and chemical mechanical polishing.

[0142] Other materials that can be polished include metals such as Si, Cu, W, Ti, Cr, Co, Zr, Hf, Mo, Ta, Ru, Au, Pt, Ag, Ni, and Al; metal compounds such as oxides, nitrides, and silicides of the aforementioned metals; and intermetallic compounds. Among these materials that can be polished, this product can be suitably used for metals and metal oxides, and is particularly suitably used for metal oxides. [Examples]

[0143] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following examples unless it exceeds the gist of the invention.

[0144] (Measurement of average secondary particle size) The average secondary particle size of silica particles in the silica sols obtained in the examples, comparative examples, and reference examples was measured using a dynamic light scattering particle size analyzer (Zetersizer Nano ZS, Malvern Panalytical).

[0145] (Measurement of average primary particle diameter) The silica sol dispersions obtained in the examples, comparative examples, and reference examples were dried at 150°C, and the specific surface area of ​​the silica particles was measured using the automatic specific surface area analyzer "BELSORP-MR1" (model name, Microtrac-Bel Corporation). The density was then calculated to be 2.2 g / cm³ using the following formula (3). 3 The average primary particle size was then calculated. Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ... (3)

[0146] (Measurement of surface silanol group density) The surface silanol group density of silica particles was measured and calculated using the Sears method under the conditions shown below. Silica sols equivalent to 1.5 g of silica particles were collected from the examples, comparative examples, and reference examples, and pure water was added to make a volume of 90 mL. Under 25°C conditions, 0.1 mol / L hydrochloric acid aqueous solution was added until the pH reached 3.6, then 30 g of sodium chloride was added, and pure water was gradually added to completely dissolve the sodium chloride. Finally, pure water was added until the total volume of the test solution reached 150 mL to obtain the test solution. The obtained test solution was placed in an automatic titrator, and a 0.1 mol / L sodium hydroxide solution was added dropwise to measure the titration volume A (mL) of 0.1 mol / L sodium hydroxide solution required to change the pH from 4.0 to 9.0.

[0147] Using the following formula (1), calculate the amount of 0.1 mol / L sodium hydroxide solution (V) consumed to change the pH of 1.5 g of silica particles from 4.0 to 9.0. Using the following formula (2), calculate the surface silanol group density ρ (particles / nm) of the silica particles. 2 ) was calculated. V=(A×f×100×1.5) / (W×C) ··· (1) A: The amount of 0.1 mol / L sodium hydroxide solution required to change the pH of 1.5 g of silica particles from 4.0 to 9.0 (mL) f: Titer of the 0.1 mol / L sodium hydroxide solution used C: Concentration of silica particles in silica sol (mass%) W: Amount of silica sol collected (g) ρ = (B × NA) / (10 18 ×M×SBET) ··· (2) The amount of sodium hydroxide (mol) required to change the pH of 1.5g of silica particles from 4.0 to 9.0, calculated from B:V. NA: Avogadro's number (particles / mol) M: Silica particle amount (1.5g) SBET: Specific surface area (m²) of silica particles measured when calculating the average primary particle diameter. 2 / g)

[0148] (Viscosity measurement) The viscosity of the silica sols obtained in the examples, comparative examples, and reference examples was measured using an E-type viscometer "TVE-25L" (model name, manufactured by Toki Sangyo Co., Ltd.) at 25°C and a shear rate of 150 / second.

[0149] [Reference example] Solution (B) was prepared by mixing 85% by mass of tetramethoxysilane and 15% by mass of methanol, and solution (C) was prepared by mixing a 2.3% by mass aqueous solution of ammonia. Solution (A), which had been pre-mixed with methanol, pure water, and ammonia, was charged into a reaction vessel equipped with a thermometer, stirrer, feed pipe, and distillation line. The methanol concentration in solution (A) was set to 87.3% by mass, the water concentration in solution (A) to 11% by mass, and the ammonia concentration in solution (A) to 1.7% by mass. While maintaining the reaction solution temperature at 44°C, 100% by mass of solution (B) and 32% by mass of solution (C) were added to 137% by mass of solution (A) at a constant rate over 147 minutes to obtain a dispersion of silica particles with a silica particle content of approximately 12.5% ​​by mass. The resulting silica particle dispersion was heated, and a portion of the dispersion medium was removed and the dispersion concentrated so that the silica particle content was approximately 17.5% by mass. Next, a substitution process was carried out to remove methanol and ammonia while adding pure water to maintain a constant volume of the silica particle dispersion. The concentration and substitution processes were carried out at atmospheric pressure and a temperature of 65-100°C. Subsequently, the silica particle dispersion was concentrated or pure water was added to obtain a silica particle dispersion (silica sol) with a silica particle content of approximately 20% by mass.

[0150] [Examples] The same process as the reference example was followed up to the substitution step. Subsequently, the silica particle dispersion was heated while increasing the temperature to 124°C at a rate of 0.23°C / min and then decreasing it to 107°C over 5 hours. After cooling, the concentration of the silica particle dispersion was adjusted to obtain a silica particle dispersion (silica sol) with a silica particle content of approximately 20% by mass.

[0151] [Comparative Example] The same process as the reference example was followed up to the substitution step. Afterward, the liquid temperature was increased at a rate of 0.25°C / min to 124°C, and the silica particle dispersion was heated while maintaining a temperature between 119°C and 124°C for 5 hours. After cooling, the silica particle dispersion was concentrated, or pure water was added, to obtain a silica particle dispersion (silica sol) with a silica particle content of approximately 20% by mass.

[0152] Table 1 shows the primary particle size, secondary particle size, average silanol group density, and viscosity of the reference example, example, and comparative example.

[0153] [Table 1]

[0154] As shown in Table 1, the silica sol in the example had low viscosity, while the silica sols in the reference example and comparative example had high viscosity. Furthermore, the surface silanol group density was lower than that of the reference example. From these results, it was found that fine-tuning the silanol group concentration and reducing viscosity by heat treatment had been difficult until now, but by performing heat treatment while lowering the temperature, both can be achieved without adding impurities such as dispersion media or salts, that is, substances that may affect the polishing of silicon wafers.

Claims

1. A method for producing silica sol, comprising the following step (1). Step (1): A step of heating a dispersion of silica particles, wherein the heating is performed while lowering the temperature at a rate of 0.001°C / min or more from the heating start temperature.

2. A method for producing silica sol according to claim 1, comprising the following step (2) before step (1) above. Step (2): A step to obtain a dispersion of silica particles containing alcohol by carrying out hydrolysis and condensation reactions of tetraalkoxysilane in the presence of an alkaline catalyst.

3. A method for producing silica sol according to claim 2, comprising the following step (3) after step (2). Step (3): A step of separating the alcohol and the alkaline catalyst from the dispersion of silica particles containing the alcohol.

4. The method for producing silica sol according to claim 2, wherein the alcohol comprises methanol.

5. The method for producing silica sol according to claim 2, wherein the alkali catalyst contains ammonia.

6. The method for producing silica sol according to claim 2, wherein the tetraalkoxysilane is tetramethoxysilane.

7. The method for producing silica sol according to claim 1, wherein the rate at which the temperature is raised to the heating start temperature is 0.1°C / min to 0.5°C / min.

8. The method for producing silica sol according to claim 1, wherein the heating start temperature is 100°C to 300°C.

9. The method for producing silica sol according to claim 1, wherein the heating time in step (1) is 5 minutes to 6000 minutes.

10. A method for producing an abrasive composition, comprising adding a silica sol obtained by the method for producing a silica sol according to any one of claims 1 to 9 to produce an abrasive composition.

11. A polishing method comprising the step of polishing using a polishing composition containing a silica sol obtained by a method for producing a silica sol according to any one of claims 1 to 9.

12. A method for manufacturing a semiconductor wafer, comprising the polishing method described in claim 11.

13. A method for manufacturing a semiconductor device, comprising the polishing method described in claim 11.

Citation Information

Patent Citations

  • Method for producing silica particles, method for producing silica sol, polishing method, method for producing semiconductor wafer, and method for producing semiconductor device

    JP2022001545A

  • Method for producing silica sol and polishing method

    JP2023004283A